Interpersonal Communication of Husband and Wife Couples Post-Infidelity in Makassar City - Supriadi M,; Abd. Rasyid Masri,; Suf Kasman, (Jurnal Mercusuar, 2022)
This research is titled "Interpersonal Communication of Married Couples After Infidelity in Makassar City," posing two research questions: 1) What is the Pattern of Interpersonal Communication Among Married Couples After Infidelity? 2) What is the Effectiveness of Interpersonal Communication Among Married Couples After Infidelity? This qualitative descriptive research employs a Communication Science approach. Primary data sources include information derived from the book "Interpersonal Communication and Infidelity," direct observation at the research location, while secondary data sources encompass documentation and literature studies to complement primary data. Data collection involves observation, interviews, and documentation. Data processing and analysis proceed through three stages: data reduction, data presentation, and drawing conclusions. Research results reveal four communication patterns among married couples in this study: balanced communication, inverted balance communication, imbalanced separation communication, and monopolistic communication. Overall, the most suitable communication pattern for married couples to maintain their relationship after infidelity is balanced communication. The effectiveness of interpersonal communication undertaken by these married couples leads to open-mindedness, empathy, patience in accepting mistakes, and being supportive. These attitudes contribute to restoring their relationship, even though occasional apprehensions and suspicions persist. Nonetheless, both partners strive to rebuild trust and offer opportunities for self-improvement. The implications of this research aim to serve as positive references and advice for married couples, encouraging them to engage in effective interpersonal communication to nurture and develop their romantic relationship, preserving their commitment and thereby reducing infidelity rates and relationship terminations resulting from infidelity.